Effect of Bromelin Enzyme Concentration on Coconut Oil Quality (Cocos Nucifera) - Farhan Dwi Permana; Supriyanto Supriyanto; Cahyo Indarto (Universitas Darussalam Gontor, 2023)
The traditional coconut oil processing process has the disadvantage of a long extraction and heating process. The use of bromelin enzyme from pineapple can speed up the extraction process in coconut oil. The use of bromelin enzymes in addition to accelerating the extraction process can also improve the quality of the oil produced. The purpose of this study is to determine the effect of the concentration of natural bromelin enzymes that can produce good quality coconut oil. The experimental design used was a randomized design complete with treatment using natural bromelin enzyme in the oil extraction process. The enzyme concentrations used were 0%, 1%, and 1.5% later compared to conventional methods. The parameters in this study include yield, moisture content, specific gravity, viscosity and freefatty acids. The data from the study were analyzed using anova α 5% if there was an effect, further tests were carried out using DMRT α 5%. The results of this study showed that different enzyme concentrations had a significant effect on the quality of coconut oil. The analysis results showed that A3 treatment (1.5% bromelin enzyme) was the best treatment compared to other treatments with a yield of 11.00±0.28; moisture content 0.05%±0.00, specific gravity 0.97±0.02; viscosity 0.78±0.02; and free fatty acid levels of .65±0.01%